Negative Impact of Parental Verbal Abuse on the Formation of Adolescent Self-Concept - Nelly Marhayati; Lailatul Badriyah; Usta Andani (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Most parents do not realize that calling a child inappropriately and comparing the child with others is verbal violence and greatly affects children's self-concept, especially adolescents. The study aimed to determine the impact of parental verbal violence on adolescent self-concept in Sumber Asri Village. This study used a quantifiable approach to 60 respondents with adolescents aged 13 and 18. Research data was obtained by filling out a questionnaire using a google form. Research instruments are arranged based on three dimensions of self-concept: knowledge, expectations, and assessment. The data were analyzed using a product moment test, where the analysis results showed a weak correlation in a negative direction of -0.205. The result means a significant negative relationship exists between parental verbal abuse and adolescent self-concept. The higher the violent verbal behavior of parents, the more negative adolescents' self-concepts. The amount of influence of 4.2% of verbal abuse can contribute to adolescent self-concept. Overcoming negative self-concept in adolescents as a result of mistakes in parenting can be done by changing the parenting style from authoritarian to democratic.